PENGEMBANGAN PEMBELAJARAN TENTANG IDENTIFIKASI TERUMBU KARANG GUNA MEMBEKALI MAHASISWA PENCINTA ALAM (MAPALA) INSTITUT AGAMA ISLAM NEGERI (IAIN) AMBON - Deli Wakano; Dece Sahertian (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Pattimura, 2022)
Indonesia is an archipelagic country consisting of 13,466 islands with a land area of 1,922,570 km2 and a water area of 3,257,483 km2. Based on Law no. 4 of 2011, that the area of coral reefs in Indonesia based on analysis of satellite imagery is around 2.5 million hectares. In addition, Indonesia is in the world's coral reef triangle area which makes Indonesia the center of world coral reef diversity with a total of 569 species belonging to 82 genera. Nonetheless, coral reefs are highly vulnerable to damage, particularly by human pressure. The partner's problem is the lack of sufficient knowledge regarding the identification of coral reefs so that there is a need for training and coaching. The solutions offered in solving partner problems include conducting: training related to how to identify coral reefs in Mamala Coastal Waters, Central Maluku, coaching related to monitoring community activities that damage coral reef ecosystems, and monitoring and evaluation of all activities that have been carried out. The resulting output is a publication in the Unpatti Ambon dedication journal (BAKTI). The implementation method is in the form of observation or initial approach to students of Nature Lovers (MAPALA) IAIN Ambon, Counseling, Training, Monitoring and Evaluation. The results achieved after the initial approach, counseling and training, Nature Lover Students (Mapala) IAIN Ambon City have the ability to identify Coral Reefs and increase knowledge about the types of Coral Reefs and the application of the Line Intercept Transect Method (LIT)